Muhammadiyah Cadre Development as an Effort to Regenerate the Progressive Islamic Movement: Literature Review - Dian Nurkholila; Rahmad Hakim (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Muhammadiyah is the largest Islamic organization and of course needs successors to continue the leadership baton. So that conducting cadre training becomes one of the means for forming militant cadres. These cadres are embryos who must be educated to become leaders and as facilitators of future leadership. For the Muhammadiyah organization, cadres have a strategic position as the main foundation in driving the Muhammadiyah movement. Cadre formation is a strategic element in maintaining the sustainability of the Muhammadiyah movement as a modern Islamic organization oriented towards renewal and empowerment of the people. This article aims to analyze the concept, strategy, and implementation of Muhammadiyah cadre formation as an effort to regenerate a progressive Islamic movement. Through a literature study approach, this research examines various literature, official documents of the Muhammadiyah Association, as well as academic findings regarding cadre education, Muhammadiyah ideology, and the organizational regeneration process. The results of the study show that Muhammadiyah cadre formation not only functions as a transmission of ideological values, but also as a process of strengthening the intellectual capacity, leadership, and professionalism of cadres. The cadre formation process takes place through formal education, autonomous organizations, formal cadre training, and the culture of the Association. Other findings show that the challenges of the digital era require innovation in training methods to be more adaptive and inclusive of the character of the younger generation.